HUBUNGAN ANTARA KEBIASAAN BELAJAR SISWA, INTENSITAS PERHATIAN ORANG TUA, DAN TINGKAT MOTIVASI BELAJAR SISWA DENGAN PRESTASI BELAJAR IPA SISWA KELAS VIII SMP TAMAN DEWASA - Desi Purnamasari; Hidayati Hidayati; Septi Ambarwati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2015)
This research is descriptively aiming to see student’s learning habit, intensity of parents’ attention and motivation level in studying science of 8th grade students of Taman Dewasa Junior High School in Umbulharjo District. Corelatively, goal of this research is to know positive relation between student’s learning habit, intensity of parents’ attention and motivation level in studying science of 8th grade students of Taman Dewasa Junior High School in Umbulharjo District, either jointly or independently. Descriptively, results show that student’s learning habit, intensity of parents’ attention and motivation level to science learning performance cathegorized as high. Correlatively, there is significant positive relation between student’s learning habit, intensity of parents’ attention and motivation level to science learning performance for 8th grade students class of 2015/2016Taman Dewasa Junior High School in Umbulharjo District, both jointly and independently.Predictors effective contribution is 33.852%, to be more specific, 5.977% for learning habits, 15.340% for intensity of parents’ attention and 12.537% for motivation level.